2020
DOI: 10.2147/jaa.s272705
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dynamic Interplay Between Microbiota and Mucosal Immunity in Early Shaping of Asthma and its Implication for the COVID-19 Pandemic</p>

Abstract: The crosstalk between host immunity and the external environment in the mucous membranes of the gastrointestinal and respiratory tracts in bronchial asthma has recently been scrutinized. There is compelling evidence that the microbiota at these sites may play an important role in the pathogenesis of this chronic airway disease. The appearance of bacteria early in life in the gut before dissemination to the airways plays a pivotal role in shaping mucosal immunity. Loss of microbial diversity or dysbiosis can re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 155 publications
0
10
0
Order By: Relevance
“…Lachnospira is a short-chain fatty acids (SCFAs) producing bacteriathat assist with gut homeostasis. Several studies have reported similar ndings among COVID-19 patients [105,110,118,119].…”
Section: Dysbiosismentioning
confidence: 55%
“…Lachnospira is a short-chain fatty acids (SCFAs) producing bacteriathat assist with gut homeostasis. Several studies have reported similar ndings among COVID-19 patients [105,110,118,119].…”
Section: Dysbiosismentioning
confidence: 55%
“…For instance, improved knowledge about the interaction between the gastrointestinal and respiratory microbiomes could serve as a foundational understanding and guide the application of oral probiotics as a treatment potential in the management of allergic disorders of the respiratory tract. 5 , 30 Similarly, a thorough understanding of how cow’s milk formula and cesarean section births result in dysbiosis and increase susceptibility to allergy and asthma development can serve as a scientific rationale for advocating for breast feeding and natural births to reduce the risk of the development of allergic diseases later in life. 31 , 32 Collectively, these examples demonstrate the important need to further develop continuing medical education curricula to include the most updated information about the role of the microbiome in disease pathogenesis as well as potential therapeutic applications to prevent the development and/or mitigate symptoms of diseases of public health importance in Saudi Arabia, such as allergies and asthma.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 Loss of these early-life microbial contacts, often caused by antibiotic misuse or cesarean section birth, can trigger an imbalance between the microbiota and a loss of microbial diversity, known as dysbiosis, and immunological aberrations that predispose children to allergies and asthma. 5 , 10 , 11 Conversely, restoring this microbial imbalance via therapeutic applications of probiotics, which are nutritional supplements containing health-promoting microbes, has yielded promising results in the management of allergy and asthma symptoms. 12 These promising scientific observations together with clinical evidence may reveal a previously unexplored role of the microbiome in immune-mediated diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Early microbial colonization of the mucous membranes, such as the respiratory system and skin, occurs in tandem with the development of the immune system. During early microbial assembly, the immune system is susceptible to the colonization of organisms due to its immaturity: The decreased secretion of cytokines results in muted inflammatory responses, which allows the settlement and expansion of the microbiome in the various niches [ 8 ]. Germ-free mice provided key evidence on the importance of the microbiota to health, as these animals showed various immune defects and increased susceptibility to infections [ 1 ].…”
Section: Microbiome and Microbiotamentioning
confidence: 99%